Responsabilidade social e dimensões sociais do marketing: o estudo de caso Furnas - Azevedo, Edinelson Benedito Alves de (2003)
The porpouse of this research was to inquire from the analysis of the corporative social performance model, taking as framework the proposal of concepts classifícation that circumscribe the social marketing dimensions inserted in the structural map's spaces structure-action of the capitalist societies in the world-wide system, if the practical of these managemental tools by FURNAS Centrais Elétricas SA, are sharpened with regulatory concepts, linked to the market, or emancipatory ones, linked to the public spirit. For in such way was fullfilled revision of the subject bibliography having such objetives: to fit the companies in the current partner-economic conjuncture, to deepen the knowledge related to the evolution of the concept of corporative social responsibility, to clarify the conceptual confusion that involves the tools that compose the social marketing dimensions and consider the analysis of the use of such tools under the approach of the Criticai Theory. It was used as method the case study, and the results had been gotten from free content analysis of controllers'speech, obtained by semi-structuralized interviews, and from documents offered by the company. The data disclose that the practical of these tools by FURNAS Centrais Elétricas SA are closer its legitimation than getting competitive advantage, so it takes to conclude that it is related to public spirit, denoting, therefore, substantives practical.